2-Deoxyglucose combined with wild type p53 over expression enhances cytotoxicity in human prostate cancer cells via oxidative stress - Ahmad, Iman M. (2007)
Over expression of the tumor suppressor gene, wild type p53 (wtp53), using adenoviral vectors (Adp53) has been suggested to kill cancer cells by hydroperoxide-mediated oxidative stress [1, 2] and nutrient distress induced by the glucose analog, 2-deoxyglucose (2DG), has been suggested to enhance tumor cell killing by agents that induce oxidative stress via disrupting hydroperoxide metabolism [3,4]. In the current study clonogenic cell killing of PC-3 and DU-145 human prostate cancer cells (lacking functional p53) mediated by 4 h exposure to 50 plaque forming units (pfus)/cell of Adp53 (that caused the enforced over expression of wtp53) was significantly enhanced by treatment with 2DG. Accumulation of glutathione disulfide was found to be significantly greater in both cell lines treated with 2DG+Adp53 and both cell lines treated with 2DG+Adp53 showed a ~2-fold increases in dihydroethidine (DHE) and 5-(and-6)-carboxy-2’,7’-dichlorodihydrofluorescein diacetate (CDCFH(2)) oxidation, indicative of increased steady-state levels of O(2)(•-) and hydroperoxides, respectively. Finally, over expression of catalase or glutathione peroxidase using adenoviral vectors partially, but significantly, protected DU-145 cells from the toxicity induced by 2DG+Adp53 treatment. These results show that treatment of human prostate cancer cells with the combination of 2DG (a nutrient stress) and over expression of the tumor suppressor gene, wtp53, enhances clonogenic cell killing by a mechanism that involves oxidative stress as well as allowing for the speculation that inhibitors of glucose and hydroperoxide metabolism can be used in combination with Adp53 gene therapy to enhance therapeutic responses.